Save life or livelihood: Responses to COVID-19 among South-Asian poor communities. Issue 2 (2nd July 2020) - Hamiduzzaman, Mohammad; Islam, M. Rezaul
ABSTRACT: We explore the COVID-19 pandemic in the way South Asian poor local communities experience health and income hazards and whether they prioritize their lives or put their lives on the line to earn a living. We conducted a descriptive analysis of the World Organizations' data, and a content analysis of health-and-income-related documents. Analysis revealed the number of COVID-19 patients and deaths is increasing in South Asia, with the presence of inconsistent lockdown measures. Major health risks (community transmission, depression, poor emergency preparedness, and inadequate acute care) and income concerns (job losses and living cost) influence the poor communities' psychosocial approach to life and livelihood. In many cases the poor communities do not follow lockdown and take matters into their own hands since the governments provide no welfare support. Our study highlights the importance of effective exit-strategy from lockdown, adequate acute care access, and food and income security for the community.